MEMPERKENALKAN RUMAH ADAT MAMASA: HUBUNGAN UKIRAN HEWAN DAN SIMBOL BUDAYA PADA BANUA SURA’ DI DESA OROBUA - Nole, Otniel Aurelius (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2024)
Mamasa’s traditional house, banua sura’, is characteristically built with beautiful and exquisite carvings, apart the building design. It appears in animal images in the form of buffaloes and horses carved based on natural materials, traditional tools, and creative and skilled specialized carvers. The carvings are not mere decoration; there are cultural symbols in the buffalo and horse carvings. The researcher introduced an indigenous Mamasa house through an investigation of the relationship between animal carvings and cultural symbols on the banua sura’ in Orobua village. The purpose of this research was explicitly to explore a Mamasa traditional house as an alternative to cultural tourism development in the Toraja tribal region. The researcher used a qualitative method with a realist ethnographic approach. The researcher collected data using observation, interview, and documentation techniques. The researcher determined the participant based on the purposive sampling technique. The researcher found that the relationship between animal carvings and cultural symbols on banua sura’ refers to the meaning of buffaloes and horses. Buffalo carvings are cultural symbols of courage and honor, while horse carvings are cultural symbols of strength. Such unique and original traditional houses can attract the attention of tourists. Ultimately, it implies opportunities and potential for the development of cultural tourism